George Gallup in Hollywood - Ohmer, Susan; Gale Group (New York Columbia University Press, 2006)
Explores the use of George Gallup's opinion polling techniques by the film industry in the 1930's and '40's. Traces Gallup's intellectual and methodological developments, examining his comprehensive approach to market research from his early education in the advertising industry to his later work in Hollywood.
Electronic reproduction.
Keywords: Gallup, George Horace -- 1901-1984.; Motion picture audiences -- United States -- Research -- History -- 20th century; Electronic books